2018
DOI: 10.1371/journal.pone.0203623
|View full text |Cite
|
Sign up to set email alerts
|

Branching morphogenesis of the urinary collecting system in the human embryonic metanephros

Abstract: An elaborate system of ducts collects urine from all nephrons, and this structure is known as the urinary collecting system (UCS). This study focused on how the UCS is formed during human embryogenesis. Fifty human embryos between the Carnegie stage (CS) 14 and CS23 were selected from the Kyoto Collection at the Congenital Anomaly Research Center of Kyoto University, Japan. Metanephroses, including the UCS, were segmented on serial digital virtual histological sections. Three-dimensional images were computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…The sample size was determined; therefore, there were at least five at each CS for statistical examinations (CS18, n = 5; CS19, n = 5; CS20, n = 5; CS21, n = 5; CS22, n = 6; CS23, n = 5). Our previous study indicated that the nephron may first appear at CS19 (Ishiyama et al ., 2018). Samples with overt damage and anomalies were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample size was determined; therefore, there were at least five at each CS for statistical examinations (CS18, n = 5; CS19, n = 5; CS20, n = 5; CS21, n = 5; CS22, n = 6; CS23, n = 5). Our previous study indicated that the nephron may first appear at CS19 (Ishiyama et al ., 2018). Samples with overt damage and anomalies were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Histological sections of the metanephros were digitalized and three‐dimensional (3D) reconstructions were generated as described previously (Ishiyama et al ., 2018, 2019). Briefly, serial transverse sections (thickness, 10 µm) of whole embryos were digitalized using an Olympus virtual slide system (VS120‐S5‐J; Olympus Corp., Tokyo, Japan) for histological observations and 3D reconstructions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations